Nonchalant Flight in Tiger Moths (Erebidae: Arctiinae) Is Correlated With Unpalatability - Dowdy, Nicolas J.; Conner, William E. (Frontiers in Ecology and Evolution, 2019)
Many aposematic animals are well-known to exhibit generally sluggish movements. However, less is known about their escape responses when under direct threat of predation. In this study, we characterize the anti-bat escape responses of 5 species of tiger moth (Erebidae: Arctiinae), a subfamily of Lepidoptera which possess ultrasound-sensitive ears. These ears act as an early-warning system which can detect the ultrasonic cries of nearby echolocating bats, allowing the moths to enact evasive flight behaviors in an effort to escape predation. We examine the role that unpalatability plays in predicting the likelihood that individuals of a given species will enact escape behaviors in response to predation. We hypothesized that more unpalatable species would be less likely to exhibit escape maneuvers (i.e., more nonchalant) than their less unpalatable counterparts. Our results demonstrate significant interspecific variation in the degree to which tiger moths utilize evasive flight behaviors to escape bat predators as well as in their degree of unpalatability. We provide evidence for the existence of a nonchalance continuum of anti-bat evasive flight response among tiger moths and show that species are arrayed along this continuum based on their relative unpalatability to bat predators. Relatively unpalatable prey more often exhibit nonchalant flight behaviors whereas palatable prey more often employ evasive dives. Our findings demonstrate that the degree to which certain animals are protected by potent chemical defenses can influence the likelihood that they will exhibit evasive escape behaviors. Further, we argue that the bat-moth predator-prey system is an ideal model for future studies of escape behaviors of prey which overcomes some of the limitations inherent to current model systems.